Infection of fattening pigs by a virulent strain of Aujeszky's disease virus and its spread in the pig - KRITAS (Σ.Κ. ΚΡΗΤΑΣ), S. K.; NAUWYNCK, H. J.; PENSAERT, M. B.; KYRIAKIS (Σ.Κ. ΚΥΡΙΑΚΗΣ), S. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this paper, the spread of the virulent 75V19 strain of Aujeszky's disease virus (ADV) in fattening pigs has been examined, and the association of this parameter to the development of relative symptoms has being sought. Four fattening pigs without antibodies against ADV have been oronasally inoculated by instillation of 1075 TCID50 of the infective strain, whilst another four seronegative pigs have been infected by the same dose of the strain administered in aerosol form. The pigs were euthanised at 4 days post inoculation and their tissues were examined by virus isolation and quantification in cell cultures. An extended spread of the virus was seen with both inoculation methods. However, the nasopharyngeal mucosa, the diaphragmatic lobes of the lungs and the pulmonary macrophages were more extensively infected in aerosol inoculated pigs compared to those of the other group. No difference was observed as regards the appearance of clinical disease between the two groups of fattening pigs. The results have also shown that, despite the high replication rate of ADV in the nasal mucosa and its ability to invade the central nervous system of fattening pigs, the degree of its replication in the nervous tissue in these pigs is limited when compared to suckling pigs.